Geoarchaeological and Bioarchaeological Studies at Mira, an Early Upper Paleolithic Site in the Lower Dnepr Valley, Ukraine. Issue 1 (12th December 2013) - Hoffecker, John F.; Holliday, Vance T.; Stepanchuk, Vadim N.; Brugère, Alexis; Forman, Steven L.; Goldberg, Paul; Tubolzev, Oleg; Pisarev, Igor
<x xml:space="preserve">Abstract</x> New geoarchaeological and bioarcheological research was undertaken at the open‐air site of Mira, which is buried in deposits of the Second Terrace of the Dnepr River, roughly 15 km downstream from the city of Zaporozhye in Ukraine. Previous excavation of the site revealed two occupation layers dating to ∼32, 000 cal BP. The lower layer (II/2) yielded bladelets similar to those of the early Gravettian, while the upper layer (I) contained traces of an artificial shelter and hundreds of bones and teeth of horse (Equus latipes). Mira represents the only firmly dated early Upper Paleolithic (EUP) site in the Dnepr Basin, and occupies a unique topographic setting for the EUP near the center of the broad floodplain of the Dnepr River. The site was visited during a period of floodplain stability, characterized by overbank deposition and weak soil formation under cool climate conditions. Mira was used as a long‐term camp, but also was the locus of large‐mammal carcass processing associated with a nearby kill of a group of horses (Layer I).